Fotografias (re)veladas em álbum de família: a tragédia rodriguiana multifacetada - Lyrio, Fernanda Maia (2011)
Using some of Nelson Rodrigues dramaturgy researchers, such as Sábato Magaldi, Eudinyr Fraga, Décio de Almeida Prado and Adriana Facina; of critics and essayists on modern tragedy as Raymond Williams and Peter Szondi; and also of critics on Rodrigues tragedy, such as Carla Souto, Elen de Medeiros and Victor Adler Pereira among other researchers on this playwriter who comes from Pernambuco, the present proposal aims to put the play Álbum de Família (1945) in Brazilian dramaturgy scenario, observing the critics position about the third and most controversial theatrical Nelson Rodrigues text, as well as the multiple faces that this tragedy assumes given the complexity of its characters and of the text itself. For textual analysis, it will be used critical and theoretical apparatus of notions on tragedy and work its context in the national scenario, pointing out some appropriation which were made by the Brazilian playwriter of the gender in question, especially considering the innovations he proposed so that the concepts of -tragic? and -tragedy? would gain more singular outlines on this studied work. Anguish of existing in Álbum de Família (1945) is a proper example of the dichotomy between the -I? and the -other?; hero and anti-hero, since the couple s photographs on the album, Jonas and D. Senhorinha, reinforce the influence of the -other? on frustrations and impossibilities of -fulfillment? of each component s ideals of an entire family structure; -deformed?, -unpleasant?, -tormented? by the tragic unit of the text performed by them.